2021
DOI: 10.1111/jeb.13889
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionary dynamics of sex‐biased genes expressed in cricket brains and gonads

Abstract: Sex‐biased gene expression, particularly sex‐biased expression in the gonad, has been linked to rates of protein sequence evolution (nonsynonymous to synonymous substitutions, dN/dS) in animals. However, in insects, sex‐biased expression studies remain centred on a few holometabolous species. Moreover, other major tissue types such as the brain remain underexplored. Here, we studied sex‐biased gene expression and protein evolution in a hemimetabolous insect, the cricket Gryllus bimaculatus. We generated novel … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 211 publications
(466 reference statements)
1
34
0
Order By: Relevance
“…Studies on CpG depletion, considered a reliable indicator of DNA methylation, have revealed that DNA methylated genes tend to perform housekeeping functions across insects including holometabolous and hemimetabolous ones (Ylla et al 2021). In addition to the epigenomics described above, the genome and transcriptome in crickets have been used for studying the sex-biased gene expression regulation, which is linked to protein sequence evolution (Whittle et al 2021a) and the relationship between codon usage frequency and expression level in different tissues and sexes (Whittle et al 2021b).…”
Section: Othersmentioning
confidence: 99%
“…Studies on CpG depletion, considered a reliable indicator of DNA methylation, have revealed that DNA methylated genes tend to perform housekeeping functions across insects including holometabolous and hemimetabolous ones (Ylla et al 2021). In addition to the epigenomics described above, the genome and transcriptome in crickets have been used for studying the sex-biased gene expression regulation, which is linked to protein sequence evolution (Whittle et al 2021a) and the relationship between codon usage frequency and expression level in different tissues and sexes (Whittle et al 2021b).…”
Section: Othersmentioning
confidence: 99%
“…To check the expression of G. bimaculatus genes in nervous systems in wild-type animals, previously generated mRNA-seq libraries were used 37 and the complete CDS for genes of interest were obtained from the recently published genome 33 . Reads were trimmed with Cutadapt v3.4 64 , and mapped to the full G. bimaculatus CDS using Geneious Read Mapper 70 .…”
Section: Methodsmentioning
confidence: 99%
“…Table S4 . Gene expression levels for osk , piwi, vasa , and CrebA/B (in FPKM per tissue) from brain and ventral cord transcriptomes of male and female adult Gryllus bimaculatus 37 . Gene IDs as per the annotated cricket genome 36 .…”
Section: Supplementary Table and File Legendsmentioning
confidence: 99%
“…Finally, protein multiple sequence alignments of orthogroups are estimated and trimmed using MAFFT ( Katoh and Standley, 2013 ) and trimAL ( Capella-Gutiérrez et al., 2009 ) respectively, to aid in identifying targeted assembled transcripts that are orthologous to the scaffold reference gene models based on the global sequence alignment coverage. A list of AssemblyPostProcessor use cases include: (1) processing de novo transcriptome assemblies to improve transcript qualities for downstream analyses ( Honaas et al., 2016 ; Yang et al., 2019 ; Whittle et al., 2021 ; and example in section 3.2.1); (2) generating matching coding sequences (CDSs) and peptide sequences in genomes with only mRNA sequences (e.g., the Malus domestica GDDH13 annotation provided only mRNA sequences but not CDSs, Daccord et al., 2017 ) and gene information gathered from databases lacking a uniformed naming system and processing protocols - for instance, the numbers of CDSs and peptides do not match in the Pyrus pyrifolia ‘Cuiguan’ genome, and the peptides are named differently from the CDSs ( Gao et al., 2021 ). The AssemblyPostProcessor -generated matching CDS and peptide sequences from the aforementioned Malus and Pyrus genomes among others provided a good starting point for the comparative genomic analyses described in section 3.2.2 and 3.2.3.…”
Section: Pipeline Implementationmentioning
confidence: 99%